Mitigation strategies for weakest bus vulnerabilities in power grids - Wu, Bo; Wang, Xiuli; Zhao, Zitong (Reliability engineering & system safety, 2026)
Ensuring the resilience of power grids against potential terrorist attacks is a critical challenge for modern energy systems. This study proposes an innovative three-stage evaluation method to identify the weakest bus in a power grid, considering the total number of affected line disconnections, the total impacted load, and the geographical extent of disruption. Experimental validation using an improved IEEE 30-bus system demonstrates the method’s effectiveness in accurately pinpointing the most vulnerable bus. Based on this assessment, a five-objective optimization framework is developed, incorporating three strategic planning measures: backup power supply deployment, preset transmission line reinforcement, and double-circuit line construction. To efficiently solve this complex sparse multi-objective mixed-integer programming problem with 490 decision variables, we introduce a novel evolutionary algorithm, PSL-SCEA. By leveraging a population of 50 individuals over 1,000,000 evolutionary evaluations, the proposed method successfully generates 15 Pareto-optimal solutions. The results demonstrate a well-balanced trade-off between economic feasibility and grid robustness, providing a strategic foundation for enhancing power grid resilience against potential disruptions. This study also investigates the scalability of the proposed method by applying it to the larger-scale IEEE 57-bus system, resulting in a set of 37 Pareto-optimal solutions. [Display omitted] •A strategic framework enhances grid resilience against terrorist threats.•A three-stage method accurately identifies the most vulnerable bus.•PSL-SCEA efficiently solves a high-dimensional sparse optimization problem.•Achieves robust and economical Pareto solutions with highly computational efficiency.